Management of the disastrous underground blowout in south of Iran - AShena, R.; Amani, M.; Taei, B.; Kamyab, Mohammadreza (Society of Petroleum Engineers, 2011)
An underground blowout is defined as an uncontrolled flow of formation fluids from a high to a low pressured zone. Due to the 9 5/8" casing collapse of the well no. X of MARUN Field with great tectonics, in the upper part of Aghajari Formation, Lahbari at 687 m depth, the formation oil and gas penetrated to Lahbari (with a large permeability and low formation mineral cementing) and appearing at the surface as 50 seeps (underground blowout). Most seeps were only 4 kms away from Jarahi River supplying the drinking water of three towns and additionally flows to Iran’ Largest Wildlife Refuge, Shadegan Refuge which is home to a large number of flora and fauna species. The gas was set ablaze by the emergency crew to secure the environment from gas spreading and explosion. The identification of the GPS seep coordinates and slope to the river, Construction of 31 soil dams in 3 days to accumulate oil in case of flows towards the river, establishment of a 85 m wide floating bridge after the heavy rain, application of a large number of busters, day and night operation of 1800 NISOC, UBD and emergency workers to cap the well were only part of these huge operations. Comprehensive geology, drilling and production history, incident, well capping and also especially HSE operations including future amendments would be described. Inexistent well integrity management (WIM) to monitor leakages, casing corrosion erosion, and cement quality after 34 years of production would be presented as the main reason of the blowout while. The evidence presented clearly shows the disobeyance of the contemporary drilling manager in not extending the 13 3/8” intermediate casing to 1200 m depth according to the geological well forecast. The previous 9 5/8” casing design was confirmed after designing it again.